Molecular Dynamics Simulations of Hyperbranched PAMAM Vicsek Fractals. Issue 2 (19th November 2014) - Fürstenberg, Florian; Gurtovenko, Andrey A.; Dolgushev, Maxim; Blumen, Alexander
Abstract : Within the broad class of hyperbranched polymers, highly symmetrical objects (such as dendrimers and Vicsek fractals) are of special theoretical interest. Here we study, using the MARTINI force‐field, polyamidoamine Vicsek fractals (PVF) in silico, focusing on their structure and dynamics in dilute solution. Our extensive microsecond‐long simulations show that the radius of gyration of PVF scales with the molecular weight as N 0.54, behavior rather close to that of stars and considerably distinct from that of dendrimers. The study of the radial density profiles indicates that different parts of the PVF interpenetrate significantly, fact which stresses the soft and sparse character of PVF. These results are also supported by our findings for the rotational autocorrelation functions. Abstract : Highly symmetrical, deterministic structures are important representatives for hyperbranched macromolecules; in particular, fractal structures cover a broad class of model polymeric systems. Here, polyamidoamine Vicsek fractals are studied by employing extensive molecular dynamics simulations along with the coarse‐grained MARTINI force‐field to unravel their structural and dynamic characteristics in dilute solution.